Planning a National-level Data Collection Protocol to Measure Outcomes for the Colorectal Cancer Control Program - Anamika Satsangi; Amy DeGroff (Georgia Southern University, 2016)
Background: The Colorectal Cancer Control Program (CRCCP) of the Centers for Disease Control and Prevention (CDC) funded 30 grantees to partner with health systems with the goal of increasing screening for colorectal cancer (CRC). Methods: Evaluators applied CDC's Framework for Program Evaluation to design a national level outcome evaluation for measuring changes in CRC screening rates in partner health systems. Results: The resulting evaluation design involves the collection and reporting of clinic-level CRC screening rates supplemented by various tools to support the reporting of high quality, reliable data. Conclusions: The CRCCP evaluation represents a strong design to measure the primary outcome of interest, CRC screening rates, and public health practitioners can benefit from lessons learned about stakeholder involvement, data quality, and the role of evaluators in data dissemination.